Miss Galaxy's Space Lessons - Phil Roxbee Cox (London, United Kingdom Scholastic, 2002)
In Miss Galaxy's Space lessons, learn about space travel when the classroom turns into a space rocket and the class nearly gets spagettified by a black hole.
Keywords: Science Fiction -- Science Fiction